Commentary: The Tyranny of Time and the Reality Principle. Issue 154 (December 2016) - Gersten, Russell
Abstract: Each of the five articles in this special issue gets "into the weeds" in terms of studying actual classroom or school implementation of evidence‐based or promising practices. Virtually all confront the issue of logistics and establishing an infrastructure for ensuring adequate implementation. In general, those studies that ask teachers to change their practice, be it core classwide instruction (Wanzek & Vaughn, this issue) or the whole‐class adolescent literacy interventions described in LaRusso et al. (this issue) experienced a good deal more in the way of implementation challenges than those that provided schools with extra services and were able to hire their own personnel to train and oversee as part of an efficacy trial. Yet, as anyone who has ever conducted an efficacy trial in the schools discovers, and Foorman et al. (this issue) remind us, research teams confront challenges never even mentioned in most research methods courses.